The Perspective of Forensic Inpatients With Psychotic Disorders on Protective Factors Against Risk of Violent Behavior - Kashiwagi, Hiroko; Yamada, Yuji; Umegaki, Yayoi; Takeda, Koji; Hirabayashi, Naotsugu (Frontiers in Psychiatry, 2020)
Background: Little is known about the opinions of forensic inpatients with psychotic disorders like schizophrenia on factors likely to prevent or decrease future violent behavior. Aims: To understand the perspectives of forensic inpatients with psychotic disorders on protective factors against risk of violent behavior and compare them to factors identified by professional staff. Method: Using the Structured Assessment of Protective Factors (SAPROF) checklist for self-appraisal of violence risk, we conducted semi-structured interviews with 32 inpatients of the Medical Treatment and Supervision Act Ward and compared the results with those of professionals. Results: Inpatients scored higher in the SAPROF total score, the motivational factors of “life goals” and “motivation for treatment,” and the protective level in general. Inpatients scored themselves lower in risk level than professionals. The degree of agreement between service users’ and professionals’ evaluations was low for all categories except external factors. Inpatients prioritized “life goals,” “self-control,” and “medication” as the top three key strengths currently preventing violent behavior, whereas the professionals selected “life goals” less often. The top three important future goals for preventing future violence selected by inpatients were “work,” “intimate relationships,” and “life goals,” with the former two being selected significantly less often by the professionals. Conclusions: This is the first study to shed light on Japanese forensic inpatients’ perspectives about preventing future violent behavior. Despite professionals’ underestimation, inpatients viewed themselves as having high motivation for treatment and positive life goals. Inpatients prioritized personal values such as life goals, work, and intimate relationships, whereas professionals prioritized understanding, treating, and observing the disease. Our findings are consistent with past reports on patients’ and clinicians’ perspectives. Awareness of such gaps in perceptions can help build fruitful therapeutic alliances. We discuss the implications in terms of treatment, how to address the gap therapeutically, and how to design treatment accordingly. Directions for future research are also discussed.